Grant proposal abstracts in science and engineering: A prototypical move-structure pattern and its variations. Issue 49 (January 2021) - Matzler, Pascal Patrick
Abstract: This study builds on existing genre analyses of research grant proposal abstracts by articulating a framework of move definitions that includes the sequencing and cycling of moves as well as their real-world or science orientation, and by exploring the tension between prototypicality and variation in these patterns. Two settings for national research grant competitions aimed at early-career scientists are introduced, namely the New Zealand Marsden award and the Chilean Fondecyt award. A framework of five constituent moves is formulated and 36 collected grant proposal abstracts are analyzed for their move-structure patterns and accompanying lexico-grammatical signals. A prototypical move-structure pattern is formulated and exemplified with abstracts from both settings and different disciplines, while key variations on this prototypical pattern are also described and analyzed. The findings suggest that a majority of abstracts are near-prototypical in structure (i.e., showing a single variation on a shared prototype) and therefore collectively maintain and reinforce this prototypical pattern as a common reference even as they individually diverge from it for their own rhetorical purposes.